Status of Geriatric Patients with Abdominal Pain Presented To Emergency Department - Lamsal, Daya Ram; Bhandari, Jeetendra (Journal of Chitwan Medical College, 2019)
Background: As the development of better health facilities with advanced tools for diagnosis and management our country is not away from global trend. Nepal’s life expectancy at birth is increasing at its pace, it has increased in about 30 years in last 4 decades. Among the various problem presenting to ED abdominal pain is one of the common complain elderly patients are greater risk of missing life-threatening causes during evaluation and investigation. The aim of the study wasEdit to identify the frequency, cause and outcome of patient presenting in Emergency department with abdominal pain. Methods: It is a retrospective study conducted in tertiary care center at Chitwan, Nepal during the period from 01/09/2017 to 30/08/2018. Electronic data entered by medical officer were retrieved and analyzed. Statistical analysis of the record was done using SPSS 16 software. Results: Elderly population who presented with chief complaints of abdominal pain was 1160 (21.79%). Among the patient presented with abdominal pain 605(52.2%) were male and 555(47.8%) were female. Mean age of patients was 71.72±8.50 years. Most common system involved was gastrointestinal and biliary problem 730(62.93%). Most common diagnosis was Urinary tract infection 269 (23.2%) among them, 487(41.98%) required hospital admission. Conclusions: Abdominal pain is one of the common presentations of elderly to emergency department. Disorders of Gastrointestinal and biliary system were among leading causes of emergency visit. Emergency physician should be tactful to identify life threatening conditions and emergency management.